KUALITAS PELAYANAN BANK DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN CUSTOMER SATISFACTION INDEX (CSI) TERHADAP KEPUASAN NASABAH - Yudi Siyamto (Jurnal Ilmiah Ekonomi Islam, 2017)
The purpose of this study was to determine the quality of services provided by the bank in serving kepusan customers using 5 dimensions of assurance, reliability, tangibility, empathy, and responsiveness, so from that dimension is unknown dimension into the client's preferences into consideration the quality of services by banks in Surakarta. The method used is the Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI) doped with Miscrosoft software Excel for Windows and SPSS for windows. Questionnaires distributed amounted to 90 respondents with a sampling with accidental sampling method. The results of data processing by using IPA (Importance Performance Analysis) obtained an average rate of 95.21% suitability. Furthermore, for the assessment of the quadrant where the priority that should be corrected is related  Equanimity  customers  and  Ease  of  providing  services.  However  the  overall  services provided  by the  bank  are  quite  satisfied  because  of  the  20  attributes,  only  the  second  to  be prioritized. It was also evident from the results of the methods CSI (Customer Satisfaction Index) indicates the level of customer satisfaction by 80.80%. The value is in the range from 66 to 80.99%, so overall customers are satisfied with the performance of the services provided by the bank in Surakarta.